Free-floating adult human brain-derived slice cultures as a model to study the neuronal impact of Alzheimer's disease-associated A beta oligomers - Mendes, Niele D.; Fernandes, Artur; Almeida, Glaucia M.; Santos, Luis E.; Selles, Maria Clara; Lyra e Silva, N. M.; Machado, Carla M. [UNESP]; Horta-Junior, Jose A. C. [UNESP]; Louzada, Paulo R.; De Felice, Fernando G.; Alves-Leon, Soniza; Marcondes, Jorge; et al. (Elsevier B.V., 2018)
Background: Slice cultures have been prepared from several organs. With respect to the brain, advantages of slice cultures over dissociated cell cultures include maintenance of the cytoarchitecture and neuronal connectivity. Slice cultures from adult human brain have been reported and constitute a promising method to study neurological diseases. Despite this potential, few studies have characterized in detail cell survival and function along time in short-term, free-floating cultures. New Method: We used tissue from adult human brain cortex from patients undergoing temporal lobectomy to prepare 200 pm-thick slices. Along the period in culture, we evaluated neuronal survival, histological modifications, and neurotransmitter release. The toxicity of Alzheimer's-associated A beta oligomers (A beta Os) to cultured slices was also analyzed. Results: Neurons in human brain slices remain viable and neurochemically active for at least four days in vitro, which allowed detection of binding of A beta Os. We further found that slices exposed to A beta Os presented elevated levels of hyperphosphorylated Tau, a hallmark of Alzheimer's disease. Comparison with Existing Method(s): Although slice cultures from adult human brain have been previously prepared, this is the first report to analyze cell viability and neuronal activity in short-term free-floating cultures as a function of days in vitro. Conclusions: Once surgical tissue is available, the current protocol is easy to perform and produces functional slices from adult human brain. These slice cultures may represent a preferred model for translational studies of neurodegenerative disorders when long term culturing in not required, as in investigations on A beta O neurotoxicity.
Keywords: Tissue slices; Organotypic culture; Human brain; Alzheimer's disease; A beta oligomers; Epilepsy